Optical coherence tomography imaging of oral benign lesions and comparison of histopathological examination - BORAHAN, MEHMET OĞUZ; ERDEM, NECİP FAZIL (My University, 2023)
Background/Aim: Optical coherence tomography (OCT) is an optical imaging method used in the examination of superficial tissues in ophthalmology, cardiology, dermatology and dentistry. It can provide high resolution microscopic images and uses infrared light. OCT was used as an auxiliary diagnostic imaging method in this study. Material and Methods: Ex vivo samples of arteriovenous malformation, odontogenic keratocyst, peripheral giant cell granuloma, pyogenic granuloma, irritation fibroma were evaluated with Swept-source OCT. The following features of altered layers were identified from OCT images: (1) irregularity, (2) fragmentation, (3) rupture, (4) interruption, (5) depression, (6) elevation, (7) thinning, (8) thickening, (9) homogeneity (10) hyperreflectivity, (11) continuity of the layers. 3D images were observed both horizontal and vertical planes. Histopathological features were compared. Results: The OCT examination of the tissues allowed to establish clear identification of the stratified squamous epithelium, lamina propria (LP) and basement membrane boundary. The darker appearance of the epithelium is directly related to its lower optical density and scattering properties, which, in turn, result in lower signal intensity. Lamina propria was observed as an hyperreflective layer and appears brighter. Continuity of the layers were well observed. Conclusions: OCT is a non-invasive and promising modality which can be used as an additional method to evaluate the characteristics of surface layers and dysplastic features of the intraoral lesions
Keywords: Arteriovenous Malformation; Odontogenic Keratocyst; Optic Coherence Tomography; Peripheral Giant Cell Granuloma